INTERACTION OF PUBLIC ORGANIZATIONS OF THE NORTH CAUCASUS FEDERAL DISTRICT: PROBLEMS, POTENTIAL, DEVELOPMENT - A. Lysenko (Современная наука и инновации, 2022)
The author presents the research of public organizations and their methods of interaction in modern Russia. It is a comparative study of the problems of public organizations in the regional space.